Utilization of telemedicine services of institute of national importance in the western region of INDIA: A mixed-method study - Krupal Joshi; Bhautik Modi; CDS Katoch (Journal of Family Medicine and Primary Care, 2024)
Introduction: Telemedicine has emerged as a crucial healthcare tool, especially during the COVID-19 pandemic, offering risk-free contactless communication between physicians and patients. In India, the introduction of official guidelines in 2019 and initiatives like the “e-Sanjeevani” national teleconsultation portal have accelerated telemedicine’s adoption. However, the utilization and satisfaction levels of telemedicine services in Institutes of National Importance (INI) remain underexplored. OBJECTIVE: This mixed-method study aims to describe the utilization of telemedicine services at the All India Institute of Medical Sciences (AIIMS), Rajkot, an INI in western India, and assess patients’ satisfaction with these services. Methods: Data was collected from patients availing telemedicine services through the e-Sanjeevani portal at AIIMS Rajkot between February and December 2022. Quantitative analysis included patient demographics, specialty attended, location, call duration, and wrong call rates. Qualitative analysis involved interviews with patients to assess their experiences and satisfaction levels. Statistical analyses were performed using SPSS for quantitative data and Atlas Ti for qualitative data. Results: A total of 12,442 doctor-to-doctor and 7,876 patient-to-doctor consultations were recorded, with a diverse age distribution (21-40 years, 45.4%). Most patients were from medical specialties, with general medicine, Pulmonary Medicine, and Dermatology being the highest. The data revealed a wide geographic distribution, with over 70% of cases from more than 200 kilometers away. Despite some challenges, including a 38.2% wrong call rate, the telemedicine services were well-received, with 96% of respondents reporting overall satisfaction. Conclusion: Telemedicine services at AIIMS Rajkot have shown high user satisfaction and accessibility, highlighting their potential in improving healthcare delivery and access, particularly in remote areas. However, efforts to enhance digital literacy and address challenges are necessary for further optimization of telemedicine services.